Plant Poisoning among Children in Rural Sri Lanka - M. B. Kavinda Chandimal Dayasiri; Shaluka F. Jayamanne; Chamilka Y. Jayasinghe (Hindawi Limited, 2017)
Plant poisoning is a common presentation in paediatric practice and an important cause of preventable mortality and morbidity in Sri Lanka. The burden of plant poisoning is largely underexplored. The current multicenter study based in rural Sri Lanka assessed clinical profiles, poison related factors, clinical management, complications, outcomes, and risk factors associated with plant poisoning in the paediatric age group. Among 325 children, 57% were male with 64% being below five years of age. 99.4% had ingested the poison. Transfer rate was 66.4%. Most had unintentional poisoning. Commonest poison plant was Jatropha circus and poisoning event happened mostly in home garden. 29% of parents practiced harmful first-aid practices. 32% of children had delayed presentations to which the commonest reason was lack of parental concern regarding urgency of seeking medical care. Presence of poisonous plants in home garden was the strongest risk factor for plant poisoning. Mortality rate was 1.2% and all cases had Oleander poisoning. The study revealed the value of community awareness regarding risk factors and awareness among healthcare workers regarding the mostly benign nature of plant poisoning in children in view of limiting incidence of plant poisoning and reducing expenditure on patient management.